Projeto - Um olhar diferente para o lixo - Manfroi, Clarinda Selos; Ávila, Lúcia Helena de Souza; Miotto, Jesuína Aparecida; Foresti, Nelci Nogueira; Oliveira, Maria Auxiliadora de; Santos, Marlene Alves dos; Simião, Regina Aparecida Versoza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> VER PDF